2023
DOI: 10.3390/plants12030687
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Symbiosis Improves Ex Vitro Acclimatization of Sugarcane Plantlets (Saccharum spp.) under Drought Stress Conditions

Abstract: The symbiotic associations between arbuscular mycorrhizal fungi (AMF) and plants can induce drought stress tolerance. In this study, we evaluated the effect of Glomus intraradices, a mycorrhizal fungus, on the ex vitro development and survival of sugarcane plantlets subjected to drought stress during the acclimatization stage of micropropagation. In vitro obtained sugarcane plantlets (Saccharum spp. cv Mex 69–290) were inoculated with different doses of G. intraradices (0, 100, and 200 spores per plantlet) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…Photosynthesis, a key primary metabolic process essential for the synthesis of energy in plant, is drastically affected by drought stress (Ilyas et al 2021). Moderate and severe levels of drought-induced decrease in leaf number and leaf area reduce the concentration of photosynthetic pigments like chlorophylls and carotenoids (Zhang et al 2018a;Mashabela et al 2023), which ultimately hampers photosynthesis in plants (Spinoso-Castillo et al 2023;El-Sawah et al 2023). Up regulated expression of chlorophyll-degrading enzymes and down regulation of chlorophyll biosynthetic enzymes also contribute to a decline in chlorophyll content (Ilyas et al 2021;Saxena et al 2022).…”
Section: Better Photosynthetic Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Photosynthesis, a key primary metabolic process essential for the synthesis of energy in plant, is drastically affected by drought stress (Ilyas et al 2021). Moderate and severe levels of drought-induced decrease in leaf number and leaf area reduce the concentration of photosynthetic pigments like chlorophylls and carotenoids (Zhang et al 2018a;Mashabela et al 2023), which ultimately hampers photosynthesis in plants (Spinoso-Castillo et al 2023;El-Sawah et al 2023). Up regulated expression of chlorophyll-degrading enzymes and down regulation of chlorophyll biosynthetic enzymes also contribute to a decline in chlorophyll content (Ilyas et al 2021;Saxena et al 2022).…”
Section: Better Photosynthetic Capacitymentioning
confidence: 99%
“…It was observed that proline content was significantly increased in Eucalyptus camaldulensis, Valeriana officinalis, Citrus aurantium, and Saccharum spp. upon inoculation with Gigaspora albida, Funneliformis mosseae, and a mixture of Glomus hoi, G. mosseae, and G. intraradices, respectively Amanifar and Toghranegar 2020;Hadian-Deljou et al 2020;Spinoso-Castillo et al 2023). The enhanced proline content in plants following AMF inoculation can be due to enhanced activity of enzyme P5CS (Δ′-pyrroline-5-carboxylate synthase), higher expression of proline biosynthetic gene encoding P5CS, enhanced activity of enzyme, glutamate dehydrogenase, and inactivation of enzyme and proline dehydrogenase (Abo-Doma et al 2011).…”
Section: Better Osmotic Adjustmentmentioning
confidence: 99%
“…antioxidants that target the excessive accumulation of reactive oxygen species [33]. Possibly, the low carotenoid content contributed to reducing the photosynthetic activity during the period of water deficit and increasing photodegradation, which resulted in a low Fv/Fm ratio.…”
Section: Resultsmentioning
confidence: 99%
“…In The degradation in the levels of chlorophyll a, chlorophyll b, and carotenoids may be due to the reduced biosynthesis of chlorophyll resulting from photochemical disturbances caused by excess light in the PSII reaction centers [32]. Carotenoids are non-enzymatic antioxidants that target the excessive accumulation of reactive oxygen species [33]. Possibly, the low carotenoid content contributed to reducing the photosynthetic activity during the period of water deficit and increasing photodegradation, which resulted in a low Fv/Fm ratio.…”
Section: Resultsmentioning
confidence: 99%
“…cv. Mex 69-290) increased the levels of proline and glycine betaine under drought stress (Spinoso-Castillo et al, 2023). Therefore, the increased level of stachydrine caused by S. indica inoculation is helpful for P. taeda seedlings under drought stress.…”
Section: Serendipita Indica-induced Drought Tolerance By Improving Bi...mentioning
confidence: 96%